Navigating the Post-Pandemic Landscape: Challenges and Strategies of a Beverage Company - Boon Keong Teow; Rashmi Chaudhary; Nur Syafarina Binti Ani; Nur Izzatul Syazirah Binti Mohamed Nizam; Nur Qisha Atierah Binti Faridzail; Nur Safirah Binti Mohd Safari; Priyanshu Mittal; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2024)
This study explores Coca-Cola's adaptive responses to challenges presented by the COVID-19 pandemic, with a focus on how targeted training programs can enhance resilience and drive innovation in areas such as supply chain management, marketing strategies, and employee adaptation. Using a mixed-method approach, the research gathered quantitative and qualitative data through Google Forms surveys and focus groups with Coca-Cola employees in Malaysia. Results highlight that supply chain disruptions and shifting consumer demands were significant obstacles, while an increased focus on employee well-being and digital transformation provided notable opportunities. Findings reveal that Coca-Cola's "well-being-first" approach and approachable leadership style positively impacted employee morale and communication. Training programs, while effective, have room for improvement in areas like digital marketing and sustainability. The study concludes that targeted training in digital literacy, supply chain management, and wellness can strengthen Coca-Cola’s adaptability in a post-pandemic environment, enhancing both workforce resilience and organizational competitiveness.